2021
DOI: 10.1039/d0sc04657d
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and kinetics of the amyloid-β peptide revealed by Markov state models based on MD data in agreement with experiment

Abstract: The convergence of MD simulations is tested using varying measures for the intrinsically disordered amyloid-β peptide (Aβ). Markov state models show that 20–30 μs of MD is needed to reliably reproduce the thermodynamics and kinetics of Aβ.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 82 publications
8
70
0
Order By: Relevance
“…Another interesting observation was that C4S was overall less flexible than H6S and C6S, even though some of the highest RMSD peaks were recorded for C4S (Figure S2). This again showed that analyzing the RMSD with respect to only one reference structure was not sufficient for characterizing molecules as flexible as GAGs, which agrees with our findings made for intrinsically disordered peptides [74].…”
Section: Rmsd-based Conformational Clusteringsupporting
confidence: 90%
See 1 more Smart Citation
“…Another interesting observation was that C4S was overall less flexible than H6S and C6S, even though some of the highest RMSD peaks were recorded for C4S (Figure S2). This again showed that analyzing the RMSD with respect to only one reference structure was not sufficient for characterizing molecules as flexible as GAGs, which agrees with our findings made for intrinsically disordered peptides [74].…”
Section: Rmsd-based Conformational Clusteringsupporting
confidence: 90%
“…Clustering at RMSD cutoff = 0.4 nm showed a convergence to a stable number of clusters for the different systems, which also indicated that the simulations reached convergence [ 74 ]. While running multiple independent simulations per system would add confidence to this conclusion, the graphs in Figure 3 obtained from single trajectories are different enough from each other to compare the results among each other—as just done—and to those obtained at other cutoff values.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations that stand on the static crystal structure can predict atomic-level motion and capture the dynamic information of conformational transitions [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] . As a result of computation and algorithmic promotion, MD simulations have become an important source of complementary information in crystallography and a primary tool for mechanism research [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] . Furthermore, MD simulations in combination with Markov state models (MSM) have widely applied to explore the thermodynamics and kinetics of biomolecules [66] , [67] and to investigate a slew of biophysical problems, such as protein folding [68] , allosteric regulation [69] , and molecular mechanism of conformational transition [70] .…”
Section: Introductionmentioning
confidence: 99%
“…Examples include replica-exchange- [50][51][52][53] and metadynamics-based methods, [54][55][56] diffusion map approaches [57][58] and Markov state modeling. [59][60][61][62] For comparisons between the methods, see for example Refs. 39 and [63][64][65] .…”
Section: Introductionmentioning
confidence: 99%